Protective effect of octreotide on intra-tracheal bleomycin-induced oxidative damage in rats - Kara, Haki; Karatas, Fikret; Tug, Tuncer; Canatan, Halit; Karaoglu, Aziz (Elsevier Gmbh, 2010)
The present study is aimed at determining the effect of parenteral octreotide against oxidative damage caused by intra-tracheal bleomycin (BLM) administration. A total of 30 male Wistar rats randomly divided into three groups (control, bleomycin alone, and bleomycin and octreotide) were used in the study. A group of animals received a single dose of intra-tracheal bleomycin (7.5 mg/kg). Animals in another group, which also received intra-tracheal bleomycin, were given 82.5 mu g/kg octreotide via i.m. injection for a week. Animals in the control group received neither bleomycin nor octreotide. All animals were sacrificed at the end of the experiment. Serum levels of malondialdehyde, vitamins A, E, and C, selenium levels were determined. In addition, glutathion peroxidase activity levels in erythrocytes were also determined. Malondialdehyde levels and glutathion peroxidase activity were increased whereas antioxidant vitamin levels were decreased significantly in animals that received only bleomycin compared to control animals (p<0.05). The values in rats that received bleomycin and octreotide were found to be closer to the control group (p<0.05). Selenium levels in animals that received only bleomycin were determined to be reduced compared to controls (p<0.05). On the other hand, selenium levels in bleomycin and octreotide groups were similar to control values in (p<0.05). In conclusion, bleomycin induces a severe stress and more importantly increases the amount of free radicals whereas octreotide administration reduces this oxidative damage significantly. (C) 2009 Elsevier GmbH. All rights reserved.
Keywords: Octreotide; Bleomycin; Antioxidant vitamins; Selenium; Molondialdehyde; GSH-Px